PENERAPAN METODE EVERYONE IS TEACHER HERE UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI CEMPAKA BARU 07 PAGI JAKARTA - Dwi Rahmah Inayati; Ati Kusmawati (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT This research is motivated by the existence of student learning outcomes in social science subjects Theme 8 Sub theme 3 Material Types of Business and Economic Activities under the KKM, so that the writer is moved to research and propose solutions by applying the Everyone is Teacher Here method. The purpose of this study was to improve social studies learning outcomes in fifth grade students at SDN Cempaka Baru 07 Pagi. The method used is classroom action research. The study was conducted in two cycles with indicators of the success of students' scores in the cognitive domain ≥ 70, in the affective domain ≥ 2.33 with the B-category, in the domain of skills category B, mastery learning ≥ 70% and learning outcomes in cycle II> of cycle I. The results showed the average value of students from 47.42 in the pre cycle increased to 49.36 at meeting 1, increased to 56.77 at meeting 2. At cycle II meeting 1 increased again to 68.55 and meeting 2 to 74,19. The percentage of pre-cycle study completion 19.35% increase in cycle I meeting 1 to 25.81%, meeting 2 to 51.61%, cycle II meeting 1 to 77.42% and meeting 2 to 80.65%. The average value of affective learning outcomes in cycle I was 3.27 (B +), then increased in cycle II to 3.52 (A). The learning outcomes of the first cycle skill get an average score in category C and increase in cycle II to category B. This shows that the everyone is Teacher Here method can improve the learning outcomes of social studies in class V students of SDN Cempaka Baru 07 Pagi. Keywords: Everyone is Teacher Here Method, Learning Outcomes, and Social Studies Subjects.